URBAN MUSLIM COMMUNITY DEVELOPMENT: A PARTICIPATORY COMMUNICATION MODEL BASED ON MOSQUES AS CENTERS FOR SOCIAL CHANGE - Pahmi, Pahmi; Hussain, Sara; Myint, Aung; Al-Zahrani, Yasir (Journal International Dakwah and Communication, 2025)
Urbanization in many Muslim-majority contexts has led to significant social challenges, including community fragmentation and economic disparity. While mosques are central spiritual hubs, their potential as catalysts for comprehensive community development is often underutilized, and conventional top-down development models frequently fail to address localized needs. This research aims to develop and validate a participatory communication model that positions the mosque as a central actor for facilitating sustainable, community-led social change. Employing a Participatory Action Research (PAR) methodology over two years in three urban Indonesian mosques, the study engaged community members and leaders through collaborative workshops and in-depth interviews. The research resulted in the “Masjid-Centric Participatory Communication (MCPC)” model, a four-stage framework encompassing mutual assessment (Ta’aruf), participatory planning (Tashawur), collaborative implementation (Tanfidz), and collective evaluation (Taqwim). Application of the model successfully initiated community-led projects in micro-finance, youth digital literacy, and environmental care, demonstrating a marked increase in social cohesion and civic engagement. The study concludes that a culturally-resonant, participatory communication model centered on the mosque can effectively transform it from a place of worship into a dynamic hub for sustainable urban development, fostering both social and spiritual well-being.